2018
DOI: 10.1002/adem.201800554
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tailored Deformation on Fatigue Strength of Austenitic 316L Stainless Steel

Abstract: Fatigue failure is one of major problems of the structural components under cyclic loading; however the fatigue test is a time-consuming and high-cost process. Therefore, it is better to establish the relationship between the fatigue property and static mechanical properties of materials. The present studies mainly focus on the relationship between fatigue strength and tensile strength of 316L austenitic stainless steel prepared with four different technologies. The rolling results in severe plastic deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The constant amplitude load (CAL), as shown in Table 3, is designed based on the linear equivalent damage theory. [23,24] The designed CAL must contribute the same fatigue damage as the acquired VAL. Then, the test load spectrums of highlow and low-high sequence forms are designed based on CAL under the condition of zero mean stress.…”
Section: Methodsmentioning
confidence: 99%
“…The constant amplitude load (CAL), as shown in Table 3, is designed based on the linear equivalent damage theory. [23,24] The designed CAL must contribute the same fatigue damage as the acquired VAL. Then, the test load spectrums of highlow and low-high sequence forms are designed based on CAL under the condition of zero mean stress.…”
Section: Methodsmentioning
confidence: 99%
“…10, fatigue cracks of L-PBF 316L SS generally initiate at the surface or the defects and fatigue damage is primarily caused by localized deformation. Increasing the work-hardening ability could effectively promote the accumulation of localized plastic deformation endurance [35], and Zhang et al [36] defined hardened strength (Δσ T ) as the difference between maximum stress and limit of elasticity to reflect the resistance to localized plastic deformation. As shown in Fig.…”
Section: Correlation Between Tensile and Fatigue Propertiesmentioning
confidence: 99%
“…Many of the above studies have shown that the initial casting microstructure will have a significant impact on the subsequent fatigue behaviors. In addition, the relationship between plastic deformation (or complex loadings) and fatigue performance has been widely reported 19–22 . It is generally believed that the larger the degree of plastic deformation, the higher the tensile strength and fatigue strength will be.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the relationship between plastic deformation (or complex loadings) and fatigue performance has been widely reported. [19][20][21][22] It is generally believed that the larger the degree of plastic deformation, the higher the tensile strength and fatigue strength will be. This is due to the high dislocation density increases the resistance to crack initiation.…”
Section: Introductionmentioning
confidence: 99%